Perspectives on metal induced crystallization of a-Si and a-Ge thin films. Issue 52 (28th November 2022) - Maity, G.; Dubey, S.; Meher, T.; Dhar, S.; Kanjilal, D.; Som, T.; Patel, Shiv P.
Abstract : Recent challenges on the metal induced crystallization (MIC) of amorphous semiconductors (a-Si and a-Ge) for potential applications in high-density data storage devices, flat panel displays, and high performance solar cells. Abstract : In recent times, the metal induced crystallization (MIC) process in amorphous semiconductors (a-Si and a-Ge) has been extensively investigated by many researchers due to potential applications of crystalline semiconductors in high-density data storage devices, flat panel displays, and high performance solar cells. In this context, we have presented a review on different schemes of MIC in metal/a-Si and metal/a-Ge bilayer films (with stacking change) on various substrates under different annealing conditions. The parameters, which limit crystallization of a-Si and a-Ge have been analyzed and discussed extensively keeping in mind their applications in solar cells and flat panel displays. The MIC of a-Si and a-Ge films under ion beam irradiation has also been discussed in detail. At the end, some suggestions to overcome the limitations of the MIC process in producing better crystalline semiconductors have been proposed. We believe that this review article will inspire readers to perform a thorough investigation on various aspects of MIC for further development of high efficiency solar cells and high quality flat panel displays.